Iron–Sulfur Cluster Protein NITROGEN FIXATION S-LIKE1 and Its Interactor FRATAXIN Function in Plant Immunity. Issue 3 (17th September 2020) - Fonseca, Jose Pedro; Lee, Hee-Kyung; Boschiero, Clarissa; Griffiths, Marcus; Lee, Seonghee; Zhao, Patrick; York, Larry M.; Mysore, Kirankumar S.
Abstract : Iron–sulfur cluster proteins play a role in plant innate immunity by regulating plant defense-related genes. Abstract: Iron–sulfur (Fe–S) clusters are inorganic cofactors that are present in all kingdoms of life as part of a large number of proteins involved in several cellular processes, including DNA replication and metabolism. In this work, we demonstrate an additional role for two Fe–S cluster genes in biotic stress responses in plants. Eleven Fe–S cluster genes, including the NITROGEN FIXATION S - LIKE1 ( NFS1 ) and its interactor FRATAXIN ( FH ), when silenced in Nicotiana benthamiana, compromised nonhost resistance to Pseudomonas syringae pv. tomato T1. NbNFS1 expression was induced by pathogens and salicylic acid. Arabidopsis ( Arabidopsis thaliana ) atnfs and atfh mutants, with reduced AtNFS1 or AtFH gene expression, respectively, showed increased susceptibility to both host and nonhost pathogen infection. Arabidopsis AtNFS1 and AtFH overexpressor lines displayed decreased susceptibility to infection by host pathogen P . syringae pv. tomato DC3000. The AtNFS1 overexpression line exhibited constitutive upregulation of several defense-related genes and enrichment of gene ontology terms related to immunity and salicylic acid responses. Our results demonstrate that NFS1 and its interactor FH are involved not only in nonhost resistance but also in basal resistance, suggesting a new role of the Fe–S cluster pathway in plant immunity.